Temper Tantrum Behavior in Early Childhood as Communication with Parents - Awanda Amelia Sadita; Nurus Sa’adah (Yayasan Insan Mulia Bima, 2023)
The role of parents is influential in early childhood development phase. Islam teaches parenting so that parents have responsibility for their children’s physical growth and psychological development. When educating children, emotional problems often arise due to mistakes in parenting, especially in communication with children. Whereas the parenting style applied by parents greatly affects changes in behavior and personality in the child. There needs to be proper handling when dealing with children who are experiencing temper tantrums. This works ia written based on a literature study that has been reviewed in accordance with scientific data that has been collected from relevant literature on the theme of discussion. The existence of good and effective communication patterns is one of the appropriate handling actions for reducing some potential for early childhood tantrums. The result of this study resulted in the existence of communication with a mindful presentation built between children and parents so that both can understand whatever is being communicated with the process of forming, delivering, receiving and processing message that occur in a person. The implications of this study are an inspiration in synergy to improve the quality of the character building process in early childhood that begins with a parenting style that is accordance with parental behavior towards children.